Instructional Strategies in Islamic Religious Education for Students with Intellectual Disabilities: A Case Study of Tanjungbalai State Special School - Fauzi Ananda; Fauziatun Azhima; Gunawan Syahputra; Shopiana; Taufik Azhar (DAAR EL-IDARAH: Journal of Islamic Education Management, 2026)
Children with special needs have characteristics and potentials that they have had since birth. In education, all children have the right to receive knowledge with special attention. Tanjungbalai City State Special School accepts students with special needs with intellectual disabilities who have IQ below average. The lack of level of understanding and concentration in communicating and absorbing knowledge is a special thing in itself. As teachers, they must make efforts so that students who have learning difficulties, especially PAI subjects, can be solved with the right strategy. This research is related to learning strategies for children with special needs with intellectual disabilities in PAI subjects at Tanjungbalai City State Special School. The purpose of this study is to describe PAI learning strategies in children with special needs with intellectual disabilities, to describe the implications and evaluation of PAI learning, and to describe PAI learning strategies. describe the supporting and inhibiting factors of learning strategies for children with special needs with intellectual disabilities in PAI subjects. This type of research is qualitative descriptive field research. Tools used in data collection in accordance with the problem to be studied include observation, interview and documentation techniques. The data sources used are primary data and secondary data. Meanwhile, in analyzing data, researchers use Miles, Hiberman, Saldana analysis techniques, which include data collection, data reduction, data presentation, and conclusions. The results showed that: 1) The learning strategy used is a demonstration strategy, this strategy emphasizes practice, the second is a behavior modification strategy which is to change student behavior in the right direction. lehi good by giving praise, and the third is a fun strategy that is playing, singing and telling stories (BMC), this strategy can foster students' enthusiasm so that does not feel bored and bored. 2) The implication of PAI learning for children with intellectual disabilities in Tanjungbalai City State Special School is that there are changes and progress of students in learning, so that it can be applied in daily life. Then for the evaluation carried out, namely in the form of written, practical and oral tests. This implementation is adjusted to the level of student ability. 3) Supporting factors that support the success of learning are students, families, especially the role of parents, and teachers. While the inhibiting factors in learning are student learning problems in their thinking skills, adjustment to the environment, and simple language and The child's speech is less clear.